Prevalence and associated factors of antibiotic self-medication and home storage among antibiotic users: a cross-sectional study in Vietnam - Dung Anh Doan; An Duc Nguyen; Giang Ba Le; Thuy Thi Xuan Nguyen; Phuong Lan Nguyen; Dai Xuan Dinh (BMC Public Health)
Abstract Background Antibiotic self-medication and home storage are two common behaviors in the community that can lead to inappropriate or unnecessary use. This study investigated the prevalence and factors associated with these two behaviors among antibiotic users in Vietnam. Methods In this cross-sectional study, 997 participants from six cities/provinces were selected using a convenience sampling method and directly interviewed from November 2023 to March 2024. Antibiotic home storage was assessed at the time of interviewing, while self-medication was assessed for the year right before this time. Factors associated with antibiotic self-medication and home storage were identified via multivariate logistic regression models and the Bayesian Model Averaging method. Results About 35.8% of the participants self-medicated with antibiotics. Among these 357 individuals, the main rationales behind this behavior were mild diseases (46.8%), time-saving (37.8%), and easy access to antibiotics from community pharmacies (33.6%). Antibiotics for self-medication were obtained mainly via community pharmacies without prescriptions (71.7%). Sore throat (45.7%), cough/common cold (42.6%), fever (37.8%), and runny nose/stuffy (31.9%) were the top four diseases/symptoms behind antibiotic self-medication. Besides, 27.3% stored antibiotics at home. Most were leftovers from previous treatments (69.1%) or deliberately reserved (33.1%). Factors associated with antibiotic self-medication included the participants’ knowledge about antibiotics (aOR = 0.96, 95%CI: 0.94–0.98), the number of people living with the participant (aOR = 1.16, 95%CI: 1.04–1.30), purchasing antibiotics without a prescription (aOR = 5.09, 95%CI: 3.78–6.85), and storing antibiotics at home (aOR = 3.52, 95%CI: 2.55–4.86). Region (north: aOR = 4.72, 95%CI: 3.15–7.08), area (urban: aOR = 0.60, 95%CI: 0.40–0.89), sharing antibiotics with others (aOR = 1.96, 95%CI: 1.38–2.79), having leftover antibiotics (aOR = 3.35, 95%CI: 2.34–4.79), and self-medicating with antibiotics in the past year (aOR = 2.97, 95%CI: 2.15–4.10) were significantly associated with home storage of antibiotics. Conclusions Antibiotic self-medication and home storage were prevalent among Vietnamese people. Health education programs should be implemented to raise public awareness about the potential risks of these two behaviors, thereby contributing to lower inappropriate antibiotic use.